Integrating a Virtual Learning Environment into an Introductory Accounting Course: Determinants of Student Motivation - De Lange, Paul (Institutional Knowledge at Singapore Management University, 2003)
Technological change is altering the way educators deliver subject content. The phenomenal growth and widespread acceptance of the Internet has seen the creation of the Virtual Learning Environment (VLE) in higher education. For the ease of integration of VLEs in higher education, software companies have provided products such as WebCT and blackboard. From a pedagogical perspective, new technologies must be evaluated in an effort to establish whether their introduction has had a beneficial impact on learning outcomes To this end, this investigation examines the attitudes of undergraduate accounting students in relation to a number of design features and attributes of WebCT (e.g. bulletin boards, on-line assessment and chat room) as a VLE. Responses from 292 on-campus undergraduate students provided data which associates four factors with improved student motivation. This study found that student satisfaction with the use of a VLE is significantly associated with the provision of: lecture notes, bulletin board, on-line assessment and other tools (chat and video summaries). The diagrammatic representation of the variables identified in this study provides a useful reference point for those educators contemplating the implementation of a VLE.